2004
DOI: 10.1021/ie0341146
|View full text |Cite
|
Sign up to set email alerts
|

Gas−Liquid Mass Transfer Studies in Sonochemical Reactors

Abstract: In the present work, quantification of the overall gas−liquid mass-transfer coefficient (K L a) in the sonochemical reactors (two different types viz. ultrasonic horn and ultrasonic bath) has been done using the dynamic method. The effect of operating parameters such as the power density into the system, gas flow rate, position of the sparger relative to the ultrasound source, and the presence of sodium chloride (as an electrolyte) on the mass-transfer coefficient has been investigated. Correlations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…4,57,59,60 There are two possible reasons. 4,16,58,59 Conclusion A robust USMR vibrating as a half wavelength resonator was designed and fabricated, according to one dimension design theory, numerical simulation and impedance analysis. Secondly, the intensification mechanism in our USMR-non-inertial cavitation with fierce surface wave oscillation and microstreaming-is more stable and uniformly distributed than in conventional reactors.…”
Section: Gas-liquid Mass Transfer Intensification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,57,59,60 There are two possible reasons. 4,16,58,59 Conclusion A robust USMR vibrating as a half wavelength resonator was designed and fabricated, according to one dimension design theory, numerical simulation and impedance analysis. Secondly, the intensification mechanism in our USMR-non-inertial cavitation with fierce surface wave oscillation and microstreaming-is more stable and uniformly distributed than in conventional reactors.…”
Section: Gas-liquid Mass Transfer Intensification Resultsmentioning
confidence: 99%
“…55 However, the improvement of mass transfer in microreactors is mainly due to the large specific surface area. 4,[57][58][59][60] In this paper, the microreactor is combined with ultrasound to intensify gas-liquid mass transfer. [51][52][53] For some reactions of faster kinetics, the mass transfer needs to be further intensified.…”
Section: Introductionmentioning
confidence: 99%
“…We point out this fact because some authors have reported the addition of an electrolyte for the enhancement of the sonochemical treatment of pollutants [48][49][50] and, therefore, a possible contribution from this must, in principle, be considered. Seymour and Gupta [48] reported enhancements of reaction rates (6-fold for chlorobenzene, 7-fold for p-ethylphenol and 3-fold for phenol oxidation), which are proportional to the diethyl ether-water partitioning coefficient of the pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…The surface tension affects the nucleation process [51] and the cavitational threshold. Other effects ascribed to the presence of electrolyte are the decrease in the gas solubility, its non-coalescing action [49] and persistence of the bubbles after insonication [50]. With this wide scenario, the disentangling of the benefits from application of the electrical field and from the presence of the background electrolyte merits a deeper analysis in further work.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, fine dispersion increases the mass transfer rate and reduces the time to reach saturation [20][21][22]. Air was used as the gas to be dissolved and water was used as the solvent.…”
Section: Introductionmentioning
confidence: 99%